Analisis Kebutuhan Pengembangan Modul Pembelajaran Biologi Bernuansa Emotional Spiritual Quotient pada Materi Perubahan dan Pelestarian Lingkungan untuk Murid Fase E - Ghina Salsabila; Heffi Alberida (LP2M UIN Ambon, 2026)
This study aims to analyze the need for a learning module with an Emotional Spiritual Quotient (ESQ) nuance as an aid in biology learning, especially on the material of environmental change and conservation for Phase E level of SMA/MA. The research method used is descriptive with quantitative and qualitative approaches. Data collection techniques were carried out through interviews with biology teachers and distributing questionnaires to Phase E students of SMA N 4 Bukittinggi. The results of this study are based on the results of teacher interviews showing that teachers in the learning process use media such as powerpoint and textbooks, but have never developed a learning module with an Emotional Spiritual Quotient (ESQ) nuance in the learning process. From these findings, it can be concluded that there is a significant need to develop a learning module with an Emotional Spiritual Quotient (ESQ) nuance.